Regulation of phosphatidylinositol 3-kinase (PI3K/Akt) pathway in chicken and duck cells and its implications for influenza A virus pathogenesis - Kumar, Sanjeeva (2018)
Wild aquatic birds, particularly ducks are considered as the major reservoirs of low-pathogenic avian influenza A viruses (LPAIAVs). Occasional spill-over to susceptible hosts like chicken and turkeys results in severe disease especially when infected with high pathogenic H5N1 virus subtypes that evolve from their progenitors LPAIAVs in gallinaceous birds, gaining zoonotic significance. Disparate disease outcomes between chicken and ducks to avian influenza virus (AIV) infection suggest potential species differences in mounting antiviral response. Mammalian studies indicate that influenza A virus non-structural protein 1 (NS1) interacts with vital host proteins to interfere with and hijack cellular functions for viral replication advantage. NS1 has been shown to bind to PI3K/Akt (phosphatidylinositol-3-kinase) p85beta subunit resulting in pathway activation. The PI3K/Akt pathway is crucial in the regulation of cellular differentiation, proliferation and survival through inhibition of pro-apoptotic factors. However, there are few studies of regulation of PI3K/Akt signalling in avian hosts, and in particular of its role in AIV replication. Understanding the host cellular response to AIV infections is key for developing effective control measures. Therefore, the present study investigated the regulation of PI3K/Akt regulation in avian cells and its implications for influenza A virus replication. Infection of primary chicken or duck embryo fibroblast (CEF/DEF) cells with A/mallard duck/England/7277/06(H2N3) virus demonstrated activation of PI3K/Akt only in the chicken but not in duck cells. The virus induced PI3K/Akt pathway activation was further confirmed by infecting cells with different low pathogenic avian influenza (LPAI) virus subtypes. Chemical inhibition of PI3K/Akt by treating infected CEFs with LY294002 resulted in significantly higher apoptosis induction and reduced infectious virus production compared to uninhibited control cells. These results suggest that activation of the PI3K/Akt pathway in infected chicken cells results in improved cellular survival allowing for enhanced virus replication. Analysis of previously published transcriptome data from IAV infected chicken and duck lung cells revealed higher expression of phosphatase and tensin homolog (PTEN) a potent PI3K/Akt negative regulator and down regulation of cytoskeletal actin remodelling associated genes like Cdc42 and RAC 1 in duck compared to chicken cells. Previous studies on AIV morphogenesis have shown roughly spherical budding virion morphology in CEFs while elongated in duck cells and speculated host factors responsible for virus morphogenesis. Based on these observations, repercussions of PI3K/Akt activation on cytoskeletal actin remodelling and virus morphogenesis in H2N3 virus infected CEFs and DEFs was studied. The results revealed loss of actin filament integrity and recorded perfectly spherical budding virion morphology upon PI3K/Akt inhibition in CEF cells. While duck cells still produced elongated viruses irrespective of PI3K/Akt inhibitor or mock treatment. Strikingly, a complete loss of cytoskeletal actin architecture was observed in virus infected duck cells irrespective of inhibitor or mock treatment. Analysis of chicken and duck PI3K/Akt p85β sequence revealed amino acid changes that may interfere AIV-NS1 binding and activation of PI3K/Akt. In particular, a highly acidic glutamic acid (E) amino acid residue at 475 position was observed across all major mammalian and avian hosts studied except ducks in which E475 residue was substituted with a non-polar valine (V) residue (E475V). However, these in silico experimental observations require further investigations. Infection of CEFs with LPAI viruses resulted in activation of PI3K/Akt for a shorter duration while recombinant H5N1 virus infection resulted in prolonged pathway activation. Infection of CEFs with chimeric(c) H9N2 virus carrying segment 8 (NS) from H5N1 (50-92) confirmed the potential contribution of H5N1-NS segment for prolonged PI3K/Akt activation. A comparative AIV NS1 sequence analysis from LPAI and HPAI viruses, revealed several amino acid differences that might contribute to prolonged PI3K/Akt activation. Interestingly, an additional SH3-binding motif-1 was observed in H5N1 (50-92) virus NS1 in comparison to other four viruses used in the study upon in silico protein binding site predictions. In conclusion, the present study revealed lack of PI3K/Akt activity despite AIV infection in duck fibroblast cells. There is an indication that there may be differences in the p85β subunit underlying these differences in the ducks conferring disease resistance compared to chickens. The study signifies host-specific viral replication strategy that may find potential use in disease control interventions in the future.